Etravirine in treatment-experienced HIV-1-infected children 1 year to less than 6 years of age. (15th July 2021) - MacBrayne, Christine E.; Rutstein, Richard M.; Wiznia, Andrew A.; Graham, Bobbie; Alvero, Carmelita G.; Fairlie, Lee; Lypen, Kathryn; George, Kathleen H.; Townley, Ellen; Moye, Jack; Costello, Diane G.; Reding, Christina A.; et al.
Abstract : Objective: To describe the pharmacokinetics, safety, and efficacy of etravirine (ETR) in HIV-infected children 1 to less than 6 years of age. Design: Phase I/II, open-label, multicenter, dose-finding study. Methods: Antiretroviral therapy (ART)-experienced children in two age cohorts (I: 2 to <6 years; II: 1 to less than 2 years) received weight-based ETR, swallowed whole or dispersed in liquid, with optimized ART including a ritonavir-boosted protease inhibitor. Intensive pharmacokinetics occurred 7–18 days after starting ETR. Participants with ETR AUC12h less than 2350 ng h/ml had a dose increase and repeat pharmacokinetics. Results: Twenty-six children enrolled and 21 (15 in cohort I and 6 in cohort II) had evaluable intensive pharmacokinetics sampling at the final weight-based dose. On the final dose, the geometric mean ETR AUC12h was 3823 ng h/ml for cohort I and 3328 ng h/ml for cohort II. Seven children (33.3%) on the final dose, all taking ETR dispersed, had an AUC12 h less than 2350 ng h/ml and underwent a dose increase. ETR AUC12 h was 3.8-fold higher when ETR was swallowed whole vs. dispersed, P less than 0.0001. On the final dose, 75 and 33.3% in cohorts I and II, respectively, had HIV-1 RNA 400 copies/ml or less or at least 2 log reductions from baseline at week 48. Three children (11.5%) experienced a grade at least 3 adverse event related to ETR but only 1 discontinued. Conclusion: ETR was well tolerated. Predefined pharmacokinetics targets were met but overall exposures were low vs. historical data in adults, particularly in young children taking dispersed tablets. A high rate of viral efficacy was observed among those aged 2 to more than 6 years but not in those less than 2 years. Abstract : Supplemental Digital Content is available in the text